Analisis Peran Kas dan Rekening Giro pada Bank Indonesia dalam Stabilitas Sistem Perbankan - Cakra Famati Harefa; Resi Restu Hia; Aldi Sitorus; E. Hamonangan Siallagan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the role of cash and current accounts at Bank Indonesia (BI) in maintaining the stability of Indonesia’s banking system by comparing practices in conventional and Islamic banks. Cash and BI current accounts are critical to liquidity management, compliance with the Statutory Reserve Requirement (GWM), and the transmission of monetary policy. The study employs a descriptive qualitative method with a case study approach focusing on Bank Mandiri (conventional) and Bank Syariah Indonesia (BSI) over the 2020–2024 period. Data were analyzed through a review of financial statements, Bank Indonesia regulations, and relevant accounting standards (PSAK for conventional banks and PSAK Syariah for Islamic banks). The findings indicate that while the core functions of cash and BI current accounts are broadly similar across both banking models, notable differences exist in accounting treatment, GWM management, and liquidity strategies. Conventional banks tend to optimize funds to enhance profitability through money market instruments, whereas Islamic banks place greater emphasis on prudence, sharia compliance, and systemic stability. These results highlight the importance of regulatory harmonization and the development of sharia-compliant liquid instruments to support a more inclusive national banking stability framework.